2020
DOI: 10.3390/cancers12102743
|View full text |Cite
|
Sign up to set email alerts
|

Protein Translation Inhibition is Involved in the Activity of the Pan-PIM Kinase Inhibitor PIM447 in Combination with Pomalidomide-Dexamethasone in Multiple Myeloma

Abstract: Background: Proviral Insertion site for Moloney murine leukemia virus (PIM) kinases are overexpressed in hematologic malignancies, including multiple myeloma. Previous preclinical data from our group demonstrated the anti-myeloma effect of the pan-PIM kinase inhibitor PIM447. Methods: Based on those data, we evaluate here, by in vitro and in vivo studies, the activity of the triple combination of PIM447 + pomalidomide + dexamethasone (PIM-Pd) in multiple myeloma. Results: Our results show that the PIM-Pd combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…Results of new pharmacological combinations of PIM447 with other anti-myeloma agents have demonstrated a synergistic effect in MM in a preclinical study [ 78 ]. This study showed that PIM447 in combination with the standard treatment pomalidomide + dexamethasone exerts a potent antitumor effect and significantly improves survival with respect to the standard treatment.…”
Section: Pim Kinase Inhibitorsmentioning
confidence: 99%
“…Results of new pharmacological combinations of PIM447 with other anti-myeloma agents have demonstrated a synergistic effect in MM in a preclinical study [ 78 ]. This study showed that PIM447 in combination with the standard treatment pomalidomide + dexamethasone exerts a potent antitumor effect and significantly improves survival with respect to the standard treatment.…”
Section: Pim Kinase Inhibitorsmentioning
confidence: 99%
“…Taken together, while PIM-inhibition showed promising activity in a phase I study, there are currently no clinical trials examining this further. While there is preclinical rationale for combining PIM-inhibition with pomalidomide and dexamethasone [ 107 ], which leads to downregulation of IRF4 and convergently inhibits protein translation through inhibition of mTORC1 and c-MYC, there are so far no studies examining combination therapies as further development of this compound has been abandoned.…”
Section: Pim-directed Therapiesmentioning
confidence: 99%
“…In line with what others proposed for different small-molecule inhibitors, the authors demonstrated a strong synergistic effect with standard of care agents (IMiDs and PIs), supporting the use of this combination to treat MM patients [ 86 ] . In fact, in a more recent publication, the same authors used one of these combinations (PIM447 plus pomalidomide and dexamethasone) and showed improved survival in a preclinical mouse model, where they revealed a convergent blockage of MYC and mTORC1, disrupting the function of eIF4e (Eukaryotic translation Initiation Factor 4E), an essential element of the Initiation Translation Complex [ 128 ] , and downregulating IRF4, important in many immune-related contexts [ 129 ] , as happened with several BETi [ 87 ] . Interestingly, Buettner et al [ 89 ] presented a similar effect by leflunomide, an orally available, non-toxic, inexpensive immunosuppressive drug regularly used to treat rheumatoid arthritis.…”
Section: Myc Inhibition Strategiesmentioning
confidence: 99%